2020
DOI: 10.1111/imm.13188
|View full text |Cite
|
Sign up to set email alerts
|

Ageing dangerously; homing of senescent CD8 T cells in cutaneous Leishmaniasis

Abstract: Summary Both CD8+ T cells and NK cells contribute to the immune response against the protozoan Leishmania parasite. Both are able to generate IFN‐γ and both display cytotoxic features. These features may enable them to not only contribute to parasite clearance but also to cause immune‐mediated pathology. This pathology is evident, for example, in the Leismania‐induced skin lesions found in patients with cutaneous leismaniasis (CL). Here we highlight new data demonstrating that CD8+ T cells and NK cells in CL d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Some authors related that T cells expressing CD57 + were shown in high frequency on CL lesions caused by L. braziliensis [21]. Corroborated with our hypothesis, Milling S. showed that in infected tissues, CD8 + CD57 + T cells are responsible for the high cytotoxicity observed in CL skin lesions and higher damage capability compared to infiltrated NK cells expressing CD57 + [25]. In fact, we find the same profile of NK cells in DL patients with less capability compared to CD8 + CD57 + T cells in both DL and CL ulcers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some authors related that T cells expressing CD57 + were shown in high frequency on CL lesions caused by L. braziliensis [21]. Corroborated with our hypothesis, Milling S. showed that in infected tissues, CD8 + CD57 + T cells are responsible for the high cytotoxicity observed in CL skin lesions and higher damage capability compared to infiltrated NK cells expressing CD57 + [25]. In fact, we find the same profile of NK cells in DL patients with less capability compared to CD8 + CD57 + T cells in both DL and CL ulcers.…”
Section: Discussionsupporting
confidence: 80%
“…CD8 + T cells expressing GzB were found on CL and DL biopsies, showing their involvement in both clinical forms of the disease [ 24 ]. Recently, Milling S reported that senescent CD8 + T cells are apparently the most important cell population mediating the disease pathology observed in CL [ 25 ]. In the present study, we evaluated the participation of senescent CD8 + T cells in the pathogenesis of DL compared to CL on peripheral blood, biopsies, stimulated in vitro cultures, and performed co-culture functional assays.…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic cells are the main cellular source of IFN-α, whereas fibroblasts are the main cellular source of IFN-β 25 . Initially, it was believed that only CD4 + T helper type 1 (Th1) lymphocytes, CD8 + cytotoxic T lymphocytes, and NK cells produce IFN-γ 26 , 27 .However, current evidence indicates that other cells such as B cells, natural killer T (NKT) cells and antigen-presenting cells (APCs) can also secrete IFN-γ 28 32 .…”
Section: Resultsmentioning
confidence: 99%
“…The low proportion of ML among young patients is well described in hospital- and field-based case series in Brazil and Bolivia 3 , 17 , 19 . The recurrence of the disease, affecting the mucosa during old age after the healing of cutaneous ulcers associated with CL, suggests that the immunosenescence phenomenon may be involved in this clinical phenotype 20 .…”
Section: Discussionmentioning
confidence: 99%